Central Sleep Apnea in Patients due to Severe Aortic Stenosis. (7th June 2010) - Prinz, Christian; Bitter, Thomas; Oldenburg, Olaf; Faber, Lothar; Horstkotte, Dieter; Piper, Cornelia
Abstract : History . We report about the course of central sleep apnea (CSA) in 3 patients (70.3 ± 15.2 years) with severe aortic stenosis (AS) (AVA ≤ 1.0 cm 2, NYHA2.7 ± 1.4 ). Investigations . Every patient received echocardiography, left/right-heart catheterization, and cardiorespiratory polygraphy before and 6 months after surgical aortic valve replacement (without right-heart catheterization during follow up). Course . Preoperatively all patients demonstrated reduced systolic left ventricular function (EF< 55 % ). They had elevated pulmoraryarterialy pressures and severe CSA. After valve replacement left ventricular function and exercise capacity improved, as well as the severity of CSA. Conclusion . Patients with severe AS can develop CSA, which seems to improve after surgery. Patients with severe AS should be screened for CSA, because CSA might be an additional risk factor and hint that myocardial adaptation is exhausting.